Developing The Cirebon City Toponymy-Based Digital Encyclopedia as a Plantae Learning Resource for the Tenth-Grade Senior High School Students - Audriansyah, Lulu Ulfah; Lesmanawati, Ina Rosdiana; Nada, Shofwatun (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This study aims to create a toponymy-based Digital Encyclopedia of the Cirebon City area which has biological elements so that it can be used as a learning resource for Plantae material for class X SMA/MA which is suitable for use in learning. This type of research is Research and Development (R&D) using the ADDIE model. The results showed that there were 9 toponyms with biological elements in the form of plant names in Harjamukti District and Kesambi District in the Cirebon City area. The development of research results into learning resources on Plantae material in the form of a Digital Encyclopedia made using software called Sketchware. The Digital Encyclopedia created and developed in the form of an application can be run on smartphones with the Android operating system. The Digital Encyclopedia is suitable for use as a learning resource for Plantae Class X SMA/MA based on validation tests and teacher and student responsesABSTRAK: Penelitian ini bertujuan untuk membuat Ensiklopedia Digital berbasis toponimi wilayah Kota Cirebon yang memiliki unsur biologis sehingga dapat dijadikan sumber belajar pada materi Plantae kelas X SMA/MA yang layak digunakan dalam pembelajaran. Jenis penelitian ini adalah Research and Development (R&D) dengan menggunakan model ADDIE. Hasil penelitian menunjukkan terdapat 9 toponimi berunsur Biologi berupa nama tumbuhan pada Kecamatan Harjamukti dan Kecamatan Kesambi di wilayah Kota Cirebon. Pengembangan hasil penelitian menjadi sumber belajar pada materi Plantae berupa Ensiklopedia Digital dibuat dengan menggunakan software bernama Sketchware. Ensiklopedia Digital yang dibuat dan dikembangkan berupa aplikasi dapat dijalankan pada smartphone dengan sistem operasi Android. Ensiklopedia Digital layak digunakan sebagai sumber belajar materi Plantae Kelas X SMA/MA berdasarkan uji validasi serta respon guru dan siswa